Repositioning Strategy in the Maritime Port Business: A Case Study from Montenegro, Port of Adria - Šekularac-Ivošević, Senka; Husić-Mehmedović, Melika; Twrdy, Elen (Promet - Traffic&Transportation, 2019)
The main objective of this paper is to define the repositioning strategy of the Port of Adria, which is the leading container maritime port of Montenegro. The strategy is an integral reflection of the analysis of internal (competitive advantage and financial strength) and external (the potential of container maritime port industry and environmental stability) repositioning criteria. The case study in this paper is mainly accomplished through the definition of specific propositions that clarify the connections between these criteria and the repositioning strategy. Knowledge and attitudes of stakeholders are used with the purpose of modeling a marketing strategy, which is based on an inductive study. The paper proposes a model based on a specific maritime port case which can be applied to any other case of maritime port repositioning as well.